Human Parechovirus 1, 3 and 4 Neutralizing Antibodies in Dutch Mothers and Infants and Their Role in Protection Against Disease. Issue 12 (December 2018) - Karelehto, Eveliina; Wildenbeest, Joanne G.; Benschop, Kimberley S. M.; Koen, Gerrit; Rebers, Sjoerd; Bouma-de Jongh, Saskia; Westerhuis, Brenda M.; de Jong, Menno D.; Pajkrt, Dasja; Wolthers, Katja C.
Abstract : Background: Human parechoviruses (HPeVs) are common pathogens in young children, and in the Netherlands, HPeV1, HPeV3 and HPeV4 are the most frequently detected genotypes. HPeV3 in particular has been associated with severe disease in young infants below 3 months of age while the other genotypes more often infect older children and elicit mild symptoms. We investigated if maternal neutralizing antibodies (nAbs) against HPeV1, HPeV3 and HPeV4 protect young Dutch infants from severe disease related to HPeV infection. Methods: We conducted a prospective case–control study of Dutch mother–infant pairs. Thirty-eight HPeV-infected infants and their mothers were included as cases, and 65 HPeV-negative children and their mothers as controls. Results: In control infants, we observed nAb seropositivity rates of 41.4%, 33.3% and 27.6%, with median nAb titers of 1:16, 1:12 and 1:8, against HPeV1, HPeV3 and HPeV4, respectively. In control mothers, nAb seropositivity rates were 84.6%, 55.4% and 60.0% with median nAb titers of 1:128, 1:32 and 1:45 against HPeV1, HPeV3 and HPeV4, respectively. The HPeV3 nAb seroprevalence was significantly lower in HPeV3-infected infants and their mothers (0.0% with P < 0.05 and 10.0% with P < 0.001, respectively). In contrast, no differences in nAb seroprevalence against HPeV1 or HPeV4 could be detected between case and control infants or mothers. Conclusions: Our results suggest that young Dutch infants are protected against severe disease related to HPeV1 and HPeV4 by maternal nAbs, but less so against HPeV3 explaining the distinct age distributions and disease severity profiles of children infected with these HPeV genotypes. Abstract : Supplemental Digital Content is available in the text.